Corn productivity in function of surface application of lime in differents management systems and cultural preparation - Narimatsu,Karem C. P. (2014)
The evaluation of technologies employed at the agricultural production system such as crop rotation and soil preparation, both associated with crop-livestock integration, is crucial. Therefore, the aim of the present study was to evaluate the incorporation of lime for three no-tillage systems and cultural managements in system of crop-livestock integration, with emphasis on corn grain yield. The experiment was conducted from January 2003 to April 2005 at Selvíria city, MS, in Dystroferric Red Latosol, clay texture. The experimental design was randomized blocks with split plots consisted of three main treatments, aimed the soil physics conditioning and the incorporation of lime: PD - No-no-tillage; CM - minimum no-tillage, and PC - conventional no-tillage; and of two secondary treatments related to the management: rotation and crop succession, with four replications. Data on agronomic traits of maize were analyzed: plant height, stem diameter, height of the first spike insertion, 100 grains weight and grain yield. The results showed that the maize produced under the system of crop-livestock integration is quite feasible, showing that grain yields are comparable to averages in the region and the different soil physical conditioning and incorporation of lime did not influence the corn yield as well as the cultural managements, rotation and succession, did not affect the maize crop behavior after two years of cultivation.